Dynamic System Analysis of Green Open Space in Medan-Indonesia - Lubis, Darwin Parlaungan; Sintong, Mahara; Nurman, Ali (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The population of Medan has been increasing from 2015 until 2019 which causes rapid and uncontrolled population and residence densification in urban area. The increase in the need for space to accommodate the increasing population growth has caused vulnerability of the change from the use of GOS (Green Open Space) to land use such as residences, industry, and services. The change in the land use will save negative impact on environmental condition if it is not handled immediately. Therefore, it is necessary to control the land use, viewed from the availability of GOS which is begun by analyzing the pattern of distribution, types, and characteristics of each GOS. The objective of the research was to analyze 1) the change in using land in each sub-district in five years (2015-2019) and 2) Some factors which influenced the dynamic change in using GOS to become used land in Medan. The research used 3 (three) stages of design: 1) literature study, 2) gathering the data (primary and secondary data), and 3) discussion on the result of processing the data. The result of the research showed that 1) Since the period of 2015-2019 Medan has experienced a very dynamic change in land use. The most significant change was as follows: residential land increased to 829 hectares, industrial land increased to 87 hectares, and service land increased to 476 hectares while vegetation land (GOS) such as wet rice field decreased to 18 hectares, mixed plantation land decreased to 116 hectares, swamp forest land decreased to 956 hectares, but dry field increased to 656 hectares, and 2) The simulation results suggest that a decline occurs in the area of green open spaces throughout the simulation year period, i.e. from 7.405 Ha (2015) to 2.023 Ha (2028); the total population during the simulation year period which formerly was equal to 2.210.624 inhabitants (2015) will have increased to 2.454.920 inhabitants (2028); while the temperature from 28.14o C (2015) increases to 28.50oC (2028); and finally, GDRP during the simulation year period which formerly was equal to IDR 164.721,82 billion (2015) increases to IDR 315,465,92 billion (2028).